Synthesis, Crystal and Molecular Structure of 1-(2-Chlorobenzyl)-2-methylthio-1H-benzimidazole - Soylu, Mustafa Serkan; Yuksektepe, Cigdem; Caliskan, Nezihe; Ozel, Sema; Servi, Suleyman (Springer/Plenum Publishers, 2011)
1-(2-Chlorobenzyl)-2-methylthio-1H-benzimidazole compound has been synthesized and characterized by elemental analysis, IR and H-1-NMR spectroscopy and single crystal X-ray diffraction. The compound crystallizes in the triclinic space group P-1 with unit cell parameters a = 17.201 , b = 5.873 , c = 24.791 , alpha = 67.410(10)A degrees, beta A = 74.083(11)A degrees, gamma A = 81.858(12)A degrees. In the crystal packing, no classic hydrogen bonds are founded, but C-H center dot center dot center dot pi interactions are being between the molecules. The molecular geometry and vibrational frequencies of (C15H13ClN2S) in the ground state have been calculated by using Hartree-Fock (HF) and Density Functional Method (DFT/B3LYP) with 6-31G(d) basis set. The optimized geometric bond lengths and bond angles obtained by using HF and DFT (B3LYP) show the best agreement with the experimental data.
Keywords: Benzimidazole; X-ray structure determination; HF; Density functional theory; Vibrational assignment